2009
DOI: 10.1371/journal.pgen.1000362
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to Submarine Hydrothermal Environments Exemplified by the Genome of Nautilia profundicola

Abstract: Submarine hydrothermal vents are model systems for the Archaean Earth environment, and some sites maintain conditions that may have favored the formation and evolution of cellular life. Vents are typified by rapid fluctuations in temperature and redox potential that impose a strong selective pressure on resident microbial communities. Nautilia profundicola strain Am-H is a moderately thermophilic, deeply-branching Epsilonproteobacterium found free-living at hydrothermal vents and is a member of the microbial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 127 publications
(197 reference statements)
5
119
0
Order By: Relevance
“…GD1, this organism was also capable of using hydrogen as an electron donor with nitrate as electron acceptor (Table S2); this has also been observed in microbes of deep-sea hydrothermal habitats (12). The presence of multiple hydrogenases in the genome (Table S3) suggests adaptations to different concentrations of hydrogen, as an important alternative electron donor, and a variety of electron acceptors (29). S. gotlandica str.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…GD1, this organism was also capable of using hydrogen as an electron donor with nitrate as electron acceptor (Table S2); this has also been observed in microbes of deep-sea hydrothermal habitats (12). The presence of multiple hydrogenases in the genome (Table S3) suggests adaptations to different concentrations of hydrogen, as an important alternative electron donor, and a variety of electron acceptors (29). S. gotlandica str.…”
Section: Resultsmentioning
confidence: 56%
“…GD1. Hydrothermal vent Epsilonproteobacteria have numerous signal sensing and transduction mechanisms, essential for free-living bacteria in highly variable environments (29,31). Compared with previously described Epsilonproteobacteria, however, the total number of protein domains involved in environmental sensing and signal transduction is notably increased in the genome of S. gotlandica str.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in the presence of sulfide, a significant amount of S 0 is transformed into soluble inorganic polysulfide (Hedderich et al, 1999). One of the mechanisms of its utilization as a terminal acceptor was described for bacterial sulfur reducers Wolinella succinogenes and Nautilia profundicola (Klimmek et al, 1998;Campbell et al, 2009). The process relies on the activity of a periplasmic sulfurtransferase/ rhodanese-like protein (Sud), which acts as a polysulfide-binding carrier and represents the actual substrate for the catalytic molybdenum (Mo)-containing subunit PsrA.…”
Section: Discussionmentioning
confidence: 99%
“…Within the Epsilonproteobacteria, the napA gene has been detected in the genomes of the rumen bacterium W. succinogenes (Simon et al, 2003); of the pathogens Helicobacter hepaticus (Suerbaum et al, 2003), Campylobacter jejuni (Parkhill et al, 2000) and several other Campylobacter spp. (Kern and Simon, 2009a); and of Arcobacter butzleri (Miller et al, 2007), Sulfurimonas denitrificans and several Epsilonproteobacteria isolated from marine geothermal environments Voordeckers et al, 2005;Nakagawa et al, 2007;Campbell et al, 2009;Sikorski et al, 2010;Giovannelli et al, 2011). The genome sequence of these organisms showed that Epsilonproteobacteria encode the periplasmic nitrate reductase, NapA, and not for the membrane-bound enzyme, NarG (in contrast to, for example, E. coli, which encodes both enzymes).…”
Section: Introductionmentioning
confidence: 99%